KAJIAN TENTANG KARAKTERISTIK PEGAWAI NEGERI SIPIL DALAM MENINGKATKAN KINERJA PEGAWAI PADA SEKRETARIAT KORPRI KABUPATEN KUTA TIMUR - Wahidah . (Jurnal Paradigma (JP), 2017)
The result shows that improvement of employee’s performance might be conducted through employee’s potency characteristic development. But there are several obstacles. It sometimes did not go with the main function, limited budget allocation for employee empowerment. So the effort to produce the professional human resources didn’t reach yet. There is still a convensional work culture, and the different perspective among unit leader in using the employees to increase work result.